FYN: emerging biological roles and potential therapeutic targets in cancer - SanFei Peng; Yang Fu (Journal of Translational Medicine, 2023)
Abstract Src family protein kinases (SFKs) play a key role in cell adhesion, invasion, proliferation, survival, apoptosis, and angiogenesis during tumor development. In humans, SFKs consists of eight family members with similar structure and function. There is a high level of overexpression or hyperactivity of SFKs in tumor, and they play an important role in multiple signaling pathways involved in tumorigenesis. FYN is a member of the SFKs that regulate normal cellular processes. Additionally, FYN is highly expressed in many cancers and promotes cancer growth and metastasis through diverse biological functions such as cell growth, apoptosis, and motility migration, as well as the development of drug resistance in many tumors. Moreover, FYN is involved in the regulation of multiple cancer-related signaling pathways, including interactions with ERK, COX-2, STAT5, MET and AKT. FYN is therefore an attractive therapeutic target for various tumor types, and suppressing FYN can improve the prognosis and prolong the life of patients. The purpose of this review is to provide an overview of FYN’s structure, expression, upstream regulators, downstream substrate molecules, and biological functions in tumors.